Después del alcalde de barrio : experiencias policiales en la Ciudad de México (1824-1861) - Diego Pulido Esteva (Centre de Recherches sur les Mondes Américains, 2017)
Regarding transformations of alcalde de barrio, this article focuses on Mexico City’s urban police during the first decades after its Independence. Its main aim is to show the fragmentation from a holist police to a specialized one. Thus, public order, security, health and ornamentation matters became in administrative and security specialized agents lacked from judicial attributes. In other words, this paper shows the transition from “neighbors” police agents to “uniformed” policemen attending rhythms, contingencies and particularities of that process. Among other contradictions, it remarks the coexistence of agents alike to alcaldes de barrio with hierarchized, waged and permanent forces. With military features, these institutions gradually displaced the Ancien Régime police system. However, such discontinuities did not modify the local scale of police power. Mainly, they brought transformations in the conception of urban police, fragmenting in a myriad of officials its original components. Thus, judicial attributes were abolished by asserting the functions related to urban order and public security.